Effect of obesity on dolutegravir exposure in Black Southern African adults living with HIV - Mondleki, Enkosi (Department of Medicine, 2023)
Background: Dolutegravir, a component of the preferred first-line antiretroviral therapy (ART) regimen has been associated with increased weight gain, which is markedly higher when combined with tenofovir alafenamide (TAF), the newer tenofovir prodrug instead of tenofovir disoproxil fumarate (TDF). South Africa has a high prevalence of obesity, especially among women. Understanding dolutegravir exposure in the patients with obesity is important for dose optimisation. Aims: We compared the pharmacokinetic parameters of dolutegravir in Southern African adults living with HIV with and without obesity. Methods: Blood samples were collected at various time points over a 24 hour-period for dolutegravir assays. Non-compartmental analysis was conducted and geometric mean ratios (GMRs), with 90% confidence intervals (CIs), were generated to compare dolutegravir pharmacokinetic parameters between the groups. Regression analyses to assess predictors of dolutegravir exposure were done. Results: 40 participants were enrolled, 26 were women and 10 had obesity. Dolutegravir area under the concentration-time curve to 24-hours (AUC0-24hr) and the maximum concentrations (Cmax) were marginally lower in participants with obesity: GMR 0.91 (90% CI, 0.71-1.16) and GMR 0.86 (90% CI, 0.68-1.07), respectively. In a multivariate linear regression analysis adjusting for age, sex, body mass index (BMI), creatinine clearance and randomisation arm (TAF or TDF), a unit increase in BMI was associated with 1.2% lower dolutegravir AUC0-24h, (P = 0.035). Conclusion: Dolutegravir exposure was marginally lower in participants with obesity, but this is not clinically significant. Our findings suggest that there is no need to dose adjust dolutegravir in people with obesity.